2017
DOI: 10.1177/2158244017704686
|View full text |Cite
|
Sign up to set email alerts
|

How Personal Factors Influence Academic Behavior and GPA in African American STEM Students

Abstract: Several theories exist that aim to identify the factors which increase the risk of STEM attrition. Several models and research frameworks aim to address student perceptions of STEM at the high-school level, develop STEM education curricula that include real-life research opportunities and everyday application, foster positive academic habit formation, improve emotional intelligence (EI), address lack of belonging in the culture of a field of study, improve growth mind-set, shift students' time perspective (TP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 83 publications
2
18
1
1
Order By: Relevance
“…Indeed, several empirical investigations have looked at the relation of mindfulness with attention control/self-regulation. The above-mentioned study by Scherer et al (2017) not only reported a positive correlation of trait mindfulness with academic success but also established how trait mindfulness was positively linked with time perspective, emotion regulation, and grit, all of which are processes relevant to self-regulation. Miller et al (2019) assigned students to either 3-minute breathing meditation at the beginning of each class over one semester or to a no-intervention condition.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Indeed, several empirical investigations have looked at the relation of mindfulness with attention control/self-regulation. The above-mentioned study by Scherer et al (2017) not only reported a positive correlation of trait mindfulness with academic success but also established how trait mindfulness was positively linked with time perspective, emotion regulation, and grit, all of which are processes relevant to self-regulation. Miller et al (2019) assigned students to either 3-minute breathing meditation at the beginning of each class over one semester or to a no-intervention condition.…”
Section: Introductionmentioning
confidence: 84%
“…There is growing empirical evidence concerning these rationales. Trait mindfulness has been associated with higher overall academic performance in cross-sectional studies (Scherer et al, 2017;Chiang and Sumell, 2019). Several experimental studies assigned a group of students 1 to either 5-20-minute breathing meditation or an active or passive control condition prior to a regular university/college course and assessed retention of course content via quiz performance at the end of the session.…”
Section: Introductionmentioning
confidence: 99%
“…According to Akbağ and Ümmet (2017) , grit and the satisfaction of basic psychological needs, as well as gender, are significant predictors of subjective well-being in young adults, having a positive and statistically significant relationship with each other. Specifically in a study among university students, Scherer et al (2017) stressed the need to structure programs that develop the dispositional factors related to grit for academic success and retention. Miller-Matero et al (2018) concluded that grit is related to academic performance, in that students who show high levels of perseverance are more likely to perform better.…”
Section: Introductionmentioning
confidence: 99%
“…The curriculums in higher education institutes are designed in a way that gets to peak and troughs in the workload of student requiring them to manage between their work-life balance, often without the support of institution. The non-cognitive personal behavior i.e., perspective of students regarding time management is also an effective predictor of educational achievement as with poor time management skills it gets difficult for students to plan their studies and which causes them anxiety and agitation at the assessment time which usually takes place at the end of the course (Scherer, Talley, & Fife, 2017). Students have previously linked negative educational results with poor time management which could be partially self-serving bias, however, there have been ample studies that establish this association (Nadinloyi et al, 2013;Kha-radze, Gulua, & Davit, 2017).…”
Section: Introductionmentioning
confidence: 99%